Editorial - Higuera-Martínez, Oscar Iván (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
Ingeniería, Investigación y Desarrollo I2+D Journal  is a publication of the Universidad Pedagógica y tecnológica de Colombia, Sogamoso Seat, aimed at inform research developments in the field of engineering and technology. In this issue, the journal offers articles in the area of engineering and technology with interdisciplinary application, in which highlights the focus on technological applications to environmental problems.